Exploring the personal philosophies of volunteerism among professors at a Malaysian research university - Adekalu, Samuel Olutokunbo (Open University of Sri Lanka, 2017)
Many argue that the changing nature of research universities globally is making the academic profession demanding. Academics are expected to do more, produce more, and ‘justify their existence’ at their respective universities often in the form of outcomes-based performance measures that are historically foreign to the academic profession. At the same time, they may have to engage in volunteerism outside the academy. Despite much existing research on volunteerism within the context of higher education, a few studies have been conducted on volunteerism among senior academics in non-Western countries, in an attempt to understand how academics balance these pluralistic roles and responsibilities, and the personal philosophy behind their ongoing engagement in volunteerism. To address this gap, this study explored the personal volunteerism philosophies of university professors from a leading research university in Malaysia. Using a purposeful sampling approach, the authors conducted in-depth, semi-structured qualitative interviews with seven professors from different academic departments who have regular engagement in volunteering activities beyond their internal academic obligations. Interviews were recorded and transcribed verbatim. From the analysis, three factors were found to contribute to the formulation of the personal philosophies about volunteerism. These were: (a) individual orientation and exposure; (b) religious beliefs; and (c) work related identities. Volunteerism was found to foster recognition for academics in their related field of expertise. The study concludes with suggestions for enhancing the volunteerism experiences of academics and implications for future research.